Neither local nor global: a political ethnography of storytelling and norm diffusion in the UNDP China - Lu, X (2019)
This dissertation examines the practice of storytelling in norm diffusion based on an in-depth political ethnography of the United Nations Development Programme (UNDP) in China. Closely engaging with glocalisation literature, this dissertation focuses on the manner in which non-linear and multidirectional norm diffusion that disrupts, fractures and transcends the local-global opposition, creating entanglements across layers of orders and scripts. Norm translators are the main actors in the mediation and communication of reframing and relocating normative packages. Empirically, this dissertation addresses the insufficient attention paid to the everyday micro-dynamics of norm diffusion, and particularly how norm circulation and contestation unfold and intensify in the context of emerging powers. The UNDP China office thus serves as an ideal case to study how such practices and processes unfold over time. My methodological approach is political ethnography, employed through a period of intensive fieldwork and participant observation carried out from 2015 to 2018, when my work at the UNDP allowed unparalleled access to materials and the internal organisational processes. My fieldwork experience highlights the critical role played by stories in translating and appropriating norms. Drawing on the theories of in-between storytelling in institutional contexts, this dissertation argues that an internalisation process of “norm metamorphosis” translates original norms into textual realities, projects and stories. These stories are normative, canonical, ambiguous, open to interpretations, and used as persuasion instruments. Detailed case studies then demonstrate the emergence and application of stories in human rights, rule of law and development cooperation. The content, form and audience of the stories are shaped by issue characteristics and ideological backgrounds, bearing the hallmarks of UNDP officials and local actors. The dissertation further describes how local norms return to the global stage through the UNDP’s narration of China’s development experience. Instead of reinforcing the local-global opposition, these stories carve out intermediary and liminal spaces through which concepts and ideas travel and transform, redefining the identity of international organisations and transnational networks in recursive conversations.